National Holidays and Collective Leave for Eid al-Fitr and Eid al-Adha Within the Framework of Religious Moderation in Indonesia - Yaqin, 'Alamul; Khasna, Syarifa (Kawanua International Journal of Multicultural Studies, 2024)
This study aims to analyze the dynamics of governing holidays and collective leave for Eid al-Fitr and Eid al-Adha, as well as their relationship to the implementation of religious moderation in Indonesia. The complexities associated with recognizing these Islamic celebrations arise from the diverse methods employed by the government, mass organizations, Islamic groups, and Sufi orders to determine the commencement of the Hijri month. A qualitative research approach was adopted, utilizing library research methods. Data were sourced from literature pertaining to governmental decisions on Eid al-Fitr and Eid al-Adha, as well as the perspectives of Nahdlatul Ulama, Muhammadiyah, Islam Aboge, and Jamaah Tarekat Naqsabandiyah Padang City. Additionally, literature on religious moderation and its application in Indonesia was examined. Findings indicate that the Indonesian Government, Nahdlatul Ulama, Muhammadiyah, Islamic Aboge, and Jamaah Tarekat Naqsabandiyah employ distinct methodologies for determining the dates of Eid al-Fitr and Eid al-Adha. The celebrations of these Islamic holidays in Indonesia align with key indicators of religious moderation, including national commitment, tolerance, non-violence, and the embrace of tradition. However, the study concludes that further interventions are necessary to mitigate potential future disputes and enhance the implementation of religious moderation in this context.